(untitled) (Fiep Bulletin - online, 2014)
The objective of the present study went analyze and to compare the Index of Corporal Mass, heart frequency and arterial pressure. In the sample, they were selecionados(as) 80 patient of both sexes, being 40 women and 40 men voluntários(as), in the age group understood among 30 to 70 years of age, neurotic and psychotic patients of the Hospital Filadélfia of the municipal district of Marechal Cândido of Rondon - PR. The used methodology was a field research, with application only of a pré tests. As instrument was used a ribbon antropometrica SANNY, it balances electronic Crystal (capacity of 150 kg). AND for aferir the arterial pressure the esfigmomanômetro was used AND to verify the heart frequency the monitor of POLAR FC it was used F1 TM. In the statistical analysis of the work the " Test " was used t " it goes Students " to have given pareados, together with the obtaining of the averages and standard deviations of the data obtained in the pré-test of the study. A level of significância of p was adopted <0,05. it was Used for statistical analysis the program Excel, Windows version 2003. It fits to stand out, that to monitor FC, it was used a portable clock that exhibits the frequency in agreement with to the intensity of the exercise. Second GUEDES et al (2003, pg. 25), it emphasizes that " the classification of the obesity is based on the amount of relative fat to the corporal weight and in the index of corporal mass (IMC)". Para the AMERICAN SCHOOL OF MEDICINE OF THE EXERCISE (2000), the obesity is associated to the increase in the risk of developing cardiovascular diseases, hypertension, diabetes, certain cancer types and of another chronic diseases. In a similar way GUEDES,... [et al] (2003, pg. 23) it emphasizes that: " the excess of corporal fat should not simply be faced as aesthetic problem. On the contrary, it is a serious disturbance of health that reduces the life expectation and he/she threatens its quality ". it Fits to stand out that, the Psychosis is a psychiatric upset, and one of the evident main characteristics in an individual, with that disturbance, is the desconexão with the reality, that is revealed in hallucinations, deliriums, and inadequate behavior. Even so Term neurosis was created by the Scottish doctor William Cullen in 1769 to indicate " disorders of senses and movement " caused by " general effects of the nervous " system. In the modern psychology, it is synonymous of psiconeurose or neurotic disturbance and he/she refers to any mental disorder that, although it causes tension, it doesn’t interfere with the rational thought or with the person’s functional capacity. To the I finish of this study, with base in the results and of the pré-test, it is ended that, with relationship to IMC (Index of Corporal Mass) they came to the average 31,83 IMC masculine sex and 23,7236 feminine sex. With relationship to the arterial pressure, it was observed that the individuals with classification of obese and obesity came high pressure above the normal. While the patients in the ideal weight obtained normal pressure.